MASJID BAITURROHIM RINGINWOK: SEJARAH, TRADISI, DAN KONTRIBUSINYA TERHADAP PERADABAN ISLAM LOKAL - Fida Qurratu Aini (JUSAN: Jurnal Sejarah Peradaban Islam Indonesia, 2026)
This study aims to examine the history, religious traditions, and contribution of the Baiturrohim Ringinwok Mosque to the development of local Islamic civilization in Ringinwok, Purwoyoso, Ngaliyan, Semarang. This study uses a qualitative method with a field study approach through observation and interviews to obtain direct data from the mosque environment and the local community. The results show that although the early history of the mosque's establishment is not fully documented, its existence has long been a center of worship activities and religious education in the community. Religious traditions such as congregational prayers, Ramadan activities (tarawih, tadarus, khotmil Qur'an), tahlilan, and the recitation of Maulid Diba' are important parts of maintaining local religious identity. In addition, the mosque contributes to strengthening religious education through children's learning activities, Qiroati recitation, and studies for parents. These findings conclude that the Baiturrohim Mosque not only functions as a place of worship, but also as a center for moral, cultural, and social development that plays a vital role in maintaining the sustainability of local Islamic traditions.